The perfect storm [videorecording (DVD)] - Clooney, George; Wahlberg, Mark, 1971-; Lane, Diane; Junger, Sebastian (Warner Home Video, 2000)
The sword-fishing boat Andrea Gail and crews attempting to rescue her struggle against a powerful North Atlantic storm.